REGULATION OF LOSS-INDUCING CRYPTO ASSET INVESTMENTS: CHALLENGES IN REGULATION, PROTECTION AND SUPERVISION - Anggasta, Giovani; Kusumadara, Afifah; Nur Widhiyanti, Hanif (International Journal of Business, Law, and Education, 2023)
Cryptocurrency has become evidence of the rapid growth of the digital economy. This phenomenon has left countries worldwide in a dilemma regarding the legal status of cryptocurrencies. Specifically in Indonesia, cryptocurrency is regulated in a limited manner, creating a gap in legal protection for investors. This research employs a normative research method with a legislative and conceptual approach. The findings of this research indicate that Indonesia tends to position cryptocurrencies in a "limited" capacity, restricting them to being considered investments rather than currency. Nevertheless, due to the legal gaps, there is a need to establish standardized, periodic, and embedded security measures overseen by Bappebti to ensure maximum protection provided by every cryptocurrency wallet service provider. Additionally, it should be mandatory for every service provider to comprehensively insure digital assets to offer financial protection to individuals.